Accurate classification of pain experiences using wearable electroencephalography in adolescents with and without chronic musculoskeletal pain - Teel, Elizabeth F.; Ocay, Don Daniel; Blain-Moraes, Stefanie; Ferland, Catherine E. (Frontiers in Pain Research, 2022)
Objective: We assessed the potential of using EEG to detect cold thermal pain in adolescents with and without chronic musculoskeletal pain. Methods: Thirty-nine healthy controls (15.2±2.1 years, 18 females) and 121 chronic pain participants (15.0±2.0 years, 100 females, 85 experiencing pain ≥12-months) had 19-channel EEG recorded at rest and throughout a cold-pressor task (CPT). Permutation entropy, directed phase lag index, peak frequency, and binary graph theory features were calculated across 10-second EEG epochs (Healthy: 292 baseline & 273 CPT epochs; Pain: 1039 baseline & 755 CPT epochs). Support vector machine (SVM) and logistic regression models were trained to classify between baseline and CPT conditions separately for control and pain participants. Results: SVM models significantly distinguished between baseline and CPT conditions in chronic pain (75.2% accuracy, 95% CI: 71.4 – 77.1%; p<0.0001) and control (74.8% accuracy, 95% CI: 66.3 – 77.6%; p<0.0001) participants. Logistic regression models performed similar to the SVM (Pain: 75.8% accuracy, 95% CI: 69.5-76.6%, p<0.0001; Controls: 72.0% accuracy, 95% CI: 64.5-78.5%, p<0.0001). Permutation entropy features in the theta frequency band were the largest contributor to model accuracy for both groups. Conclusions: Our results demonstrate that subjective pain experiences can accurately be detected from electrophysiological data, and represent the first step towards the development of a point-of-care system to detect pain in the absence of self-report.